Logics for unconventional computing. Issue 3 (4th May 2018) - Schumann, Andrew
Abstract: Logics for unconventional computing is an interdisciplinary research area which brings together computer scientists and engineers dealing with unconventional computing (such as biological, bio-inspired, chemical, physical, etc. computing) with logicians dealing with non-classical logical, algebraic, co-algebraic, and topological methods to initiate the development of novel nature-inspired computation paradigms. This paper is a Preface to the special issue devoted to Logics for unconventional computing. Graphical Abstract: